Fault Tolerant Ancillary Function of Power Converters in Distributed Generation Power System within a Microgrid Structure. (8th May 2013) - Di Tommaso, Antonino O.; Genduso, Fabio; Miceli, Rosario; Galluzzo, Giuseppe Ricco
Abstract : Distributed generation (DG) is deeply changing the existing distribution networks which become very sophisticated and complex incorporating both active and passive equipment. The simplification of their management can be obtained assuming a structure with small networks, namely, microgrids, reproducing, in a smaller scale, the structure of large networks including production, transmission, and distribution of the electrical energy. Power converters in distributed generation systems carry on some different ancillary functions as, for example, grid synchronization, islanding detection, fault ride through, and so on. In view of an optimal utilization of the generated electrical power, fault tolerant operation is to be considered as a suitable ancillary function for the next future. This paper presents a complete modeling of fault tolerant inverters able to simulate the main fault type occurrence and a control algorithm for fault tolerant converters suitable for microgrids. After the model description, formulated in terms of healthy device and leg binary variables, and the illustration of the fault tolerant control strategy, the paper shows how the control preserves power quality when the converter works in the linear range. The effectiveness of the proposed approach and control is shown through computer simulations and experimental results.